Paleohydrological changes in the Eastern Mediterranean region during the early to mid-Holocene recorded in plant wax n-alkane distributions and [delta]13 C TOC: new data from Tenaghi Philippon, NE Greece - Schemmel, Fabian; Koutsodendris, Andreas; Pross, Jörg (Organic geochemistry, 2017)
Holocene climate dynamics have strongly influenced precipitation patterns in the Eastern Mediterranean region. This holds particularly true for the ‘8.2kyrBP climatic event’, arguably the strongest perturbation of early to mid-Holocene climate. Here we present a biomarker record of leaf wax-derived n-alkane distributions and stable isotopic composition of total organic carbon (δ13CTOC) along with palynological data from the fen peat archive of Tenaghi Philippon (TP), NE Greece, spanning the interval from 8.7 to 7.5kyrBP. Our record documents the response of in situ vegetation within the Philippi peatland to changing hydrological conditions, and addresses the applicability of organic proxies such as the ‘aquatic index’ (Paq), average chain length (ACL) and δ13CTOC as indicators of peat surface moisture conditions at the study site. The long chain n-alkanes (n-C27, n-C29 and n-C31) typical of vascular terrestrial plants, dominated the peat sequence. A period of relatively dry surface conditions, indicated by low values of Paq and elevated ACL values, in concert with elevated δ13CTOC values, preceded the 8.2kyrBP climatic event from ca. 8.7 to 8.2kyrBP. Slightly wetter, more humid conditions, suggested by an increase in Paq as well as reduced ACL and δ13CTOC values, characterized the interval of the 8.2kyrBP climatic event. Notably, the increase in surface wetness, as indicated by the biomarker record, coincided with a marked rise in fern spore proportion as well as increasing proportion of pollen from aquatic taxa. Following the 8.2kyrBP event, a distinct change in paleohydrology at TP became apparent from ca. 7.9kyrBP onward. An increase in the abundance of the mid-chain length n-alkanes (n-C23 and n-C25), indicative of an increased contribution from aquatic plants to the sediment, together with a steep increase in Paq and a decrease in ACL, as well as variation in δ13CTOC, imply considerably elevated surface moisture levels, likely caused by the increased activity of the karstic system of the surrounding mountains. Collectively, the biomarker proxies and pollen data reveal a concise picture of changing moisture conditions at TP in response to the 8.2kyrBP climatic event.